PENGARUH PROMOSI JABATAN DAN PENGAWASAN YANG DILAKUKAN PIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI DI DINAS PENDIDIKAN PROVINSI SUMATEA BARAT - Emi Susanti; Rini Sarianti (Universitas Negeri Padang, 2019)
This research was conducted to find out (1) the effect of job promotion on job satisfaction (2) the effect of supervisory conducted by leaders on employee job satisfaction. This research is descriptive associative. The population in this study were employees of the Education Office of West Sumatra Province with 182 employees. The total sample is determined using the Slovin formula and proportional random sampling cluster. From this pattern, 125 employees were obtained as research samples. The data collection technique used in this study was a questionnaire. The validity test instrument uses Collected Item-Total Colleration and for reliability testing using alpha coefficient formula. Prerequisite tests were carried out by normality test, heterocedasticity test, and multicollinearity test. The technique used to analyze data is multiple regression analysis. Based on this study, it was found that (1) Job promotion had a significant effect on employee job satisfaction in the West Sumatra Provincial Education Office (2) Supervision conducted by the leadership had a significant effect on employee job satisfaction in the West Sumatra Provincial Education Office.Keywords: Job Promotion, Supervision by Leaders, Job Satisfaction